Penggunaan media pembelajaran berbasis augmented reality terhadap peningkatan pemahaman Bhinneka Tunggal Ika siswa SMA - Siti Sovia; Supentri Supentri; Indra Primahardani (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to examine the impact of Augmented Reality (AR)-based learning media on enhancing students' comprehension of Bhinneka Tunggal Ika concepts among tenth-grade students at SMA Negeri 2 Kubu Babussalam, Rokan Hilir Regency. A quantitative approach was applied utilizing a quasi-experimental design with Pretest-Posttest Control Group format. The research sample comprised 60 students divided into an experimental group (30 students) receiving AR-based instruction and a control group (30 students) undergoing conventional learning methods. Data were collected through written tests (pretest and posttest), questionnaires, classroom observation sheets, and documentation. Statistical analyses included the Shapiro-Wilk normality test, Levene's homogeneity test, and Independent Sample T-Test using SPSS 26. Findings revealed that the mean posttest score of the experimental group (83.10) surpassed that of the control group. The t-value was 5.111 with a significance level of 0.000 (< 0.05), resulting in rejection of H₀ and acceptance of H₁. The experimental group's N-Gain score reached 0.7609 (76.09%), classified as high. These results confirm that AR-based learning media exerts a meaningful and positive influence on students' understanding of Bhinneka Tunggal Ika values.